1998
DOI: 10.1111/j.1444-0938.1998.tb06745.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with narrow angles and acute angle‐closure glaucoma

Abstract: Background: Acute closure of the anterior chamber angle can have catastrophic consequences for vision when it occurs in an unsupervised situation. Visual debilitation is much less likely to result when angle-closure occurs in a well-controlled environment that allows appropriate management. Therefore, it is desirable for optometrists to undertake a complete ocular health assessment, including mydriatic fundus examination, on patients who have narrow anterior chamber angles, provided that appropriate precaution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The primary outflow pathway is through the trabecular meshwork, with a small percentage (10%) exiting via the uveoscleral route. Thus, any resistance in the outflow (e.g., blockage in trabecular meshwork) or a change in the anatomic relationship between the pupillary margin and the lens will result in IOP elevation [4042]. …”
Section: Iop Elevation and The Ergmentioning
confidence: 99%
“…The primary outflow pathway is through the trabecular meshwork, with a small percentage (10%) exiting via the uveoscleral route. Thus, any resistance in the outflow (e.g., blockage in trabecular meshwork) or a change in the anatomic relationship between the pupillary margin and the lens will result in IOP elevation [4042]. …”
Section: Iop Elevation and The Ergmentioning
confidence: 99%
“…17 18 22 The mechanisms of this phenomenon were thought to be caused by the sudden decrease of IOP due to ciliary body shutdown induced by the prolonged attack, and alteration in the capillary permeability after ischaemia of ciliary body. [23][24][25] And it was reported that the suppression of aqueous humour may persist for 1 week in most cases after the halt on aqueous suppressants, thus causing the transient IOP reduction. 17 In the present study, we did not find SCE in our patients prior LDTSCP, and we found that eyes with more audible 'bursts' and CBD had more severe SCE and greater levels of IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…5 Immediate intravenous administration of mannitol, a hyperosmotic agent, is the standard treatment. 6 However, alternative treatments should be considered if the patient is at high risk of a reaction to mannitol, such as congestive heart failure, chronic renal insufficiency, or other systemic illnesses. 7e9 In order to relieve the symptoms and lower IOP as quickly as possible, immediate anterior chamber paracentesis (ACP) has recently been suggested as an alternative treatment for patients with acute PACG.…”
Section: Introductionmentioning
confidence: 99%